Demographic and clinical features of systemic sclerosis patients with anti‐RNA polymerase III antibodies. Issue 2 (6th December 2014) - Motegi, Sei‐ichiro; Toki, Sayaka; Yamada, Kazuya; Uchiyama, Akihiko; Ishikawa, Osamu
Abstract Anti‐RNA polymerase III antibody (RNAP) is primarily detected in diffuse cutaneous type systemic sclerosis (dcSSc) patients and strongly associated with renal crisis. Additionally, there has been increasing evidence that cancer in SSc patients is associated with RNAP. The aim of this study was to examine the demographic and clinical features of SSc patients with RNAP. Among 246 SSc patients, 5.7% were positive for RNAP, 20.7% were positive for anti‐topoisomerase I antibody (Topo I) alone and 39.4% were positive for anticentromere antibody (ACA) alone. The modified Rodnan total skin score (mRTSS) in SSc patients with RNAP (19.1 ± 2.6) was significantly higher than those in SSc patients with Topo I (11.5 ± 1.1) and patients with ACA (4.4 ± 0.4). Furthermore, among SSc patients with RNAP, the levels of RNAP were positively correlated with mRTSS. Renal crisis is also significantly more prevalent in SSc patients with RNAP than patients without RNAP. Male sex, dcSSc subtype, digital vasculopathy, including digital ulcers and acro‐osteolysis, interstitial lung disease and rheumatoid arthritis complications were prevalent in SSc patients with RNAP and patients with Topo‐I. Primary biliary cirrhosis and Sjögren's syndrome were more in SSc patients with RNAP and patients with ACA compared with patients with Topo 1. No significant difference in the frequency of complications, including Raynaud's phenomenon, pulmonary artery hypertension and malignancy was observed between the three groups. Thus, measurement of RNAP in SSc patients is useful for the diagnosis and risk stratification of severe manifestation, such as renal crisis and severe skin sclerosis.